What makes a tactile forager join mixed-species flocks? A case study with the endangered Crested Ibis (Nipponia nippon). (22nd March 2017) - Ye, Yuanxing; Jiang, Yiting; Hu, Canshi; Liu, Yao; Qing, Baoping; Wang, Chao; Fernández-Juricic, Esteban; Ding, Changqing
Abstract: Visual foragers joining mixed-species flocks can enhance foraging and obtain antipredator benefits. However, relatively little is known about the benefits that tactile foragers may obtain by joining mixed-species groups. We investigated the foraging and antipredator benefits that the Crested Ibis ( Nipponia nippon ), an endangered species, may get while foraging in single-species flocks and in mixed-species flocks with Little Egrets ( Egretta garzetta ) during the nonbreeding season. We found that in single-species flocks ibises decreased the proportion of time spent vigilant and increased that spent foraging as total flock size increased. Flight initiation distance (FID, distance between a threat and the animal when the latter flees) decreased with flock size particularly in single-species flocks and alert distance (AD, distance between a threat and the animal first exhibiting alert behavior) decreased with flock size in both single- and mixed-species flocks, but was greater in mixed-species flocks. Taken together, these findings suggest that Crested Ibises may use risk dilution, but not collective detection, in single-species flocks, but use dilution, collective detection, and early warning in mixed-species flocks. We also found partial support for the resource exploitative competition hypothesis as probing bout duration increased with flock size. This tactile forager may benefit from joining mixed-species flocks with a visual forager by using collective detection and early warning (responding to the antipredator signals of the other species), but also tolerate some intraspecific competition in mixed-species flocks through resource depletion effects. Our findings have management implications that could be applied to the protection of this endangered species.